ECM Trends - Fuesz, Bill (KM world, 2021)
Search by Context: Users can find documents through a "what" search versus a traditional "where" search to offer a more efficient and accurate data exercise. * Leverage Metadata: Advancements around metadata usage enables a boost in custom search abilities. * Content from Any Location Via a Single Application: Advanced ECM solutions offer the ability to maintain content in its original repository and prevent time-consuming (and costly) data migrations through the use of plug-ins and ECM advancements that search data across silos and distribute it to a central i location for access. : Mobility in the Workplace Mobilizing the tools employees use can i ensure a high level of productivity and en-gagement by enabling access to data and : workflows anytime, anywhere. In addition to improved productivity and reduced human errors, applying AI and ML to content is helping users extract insight from unstructured data, accelerate business processes, and distribute order to databases. Consider the following ECM-related features fueled by AI and ML: * Digitization Acceleration: As companies convert text, images and other media into digital form, AI and ML can spur the process of organizing this content. * Intelligent Indexing: Applied to such processes as document scanning, AI/ML trains systems to automatically capture specific content and then independently initiate workflows. * Self-learning: These techniques automatically search for relevant index terms in similar documents.